Application of the Swiss Fiscal Rule to Artificial Data: A Monte Carlo Simulation - Alain Geier (Swiss Journal of Economics and Statistics, 2012)
The Swiss fiscal rule or "debt brake" is applied to simulated data of economic output and fiscal revenues. The budget remains almost perfectly balanced and the debt ratio stable over the medium and long term: The cyclical adjustment of the debt brake is effective in terms of its primary objective of achieving a balanced budget over the medium term. The rule also performs well with respect to the objective of taking into account the position of the economy in the cycle. In the case of a non-stationary GDP series, however, this result can not be guaranteed anymore.
Keywords: H61; E62; 330; Balanced Budget; Debt; Deficit; Budgeting; Business Cycle